Promising Practices to Eliminate Tobacco Disparities Among Asian American, Native Hawaiian and Pacific Islander Communities. Issue 5 (September 2013) - Lew, Rod; Chen, W. William
Tobacco use continues to be the single most preventable cause of death for all groups in the United States, including Asian Americans (AAs) and Native Hawaiians and Pacific Islanders (NHPIs). Despite efforts in tobacco control over the past two decades, tobacco-related health disparities remain in some priority population groups, including AAs and NHPIs. This special supplement features strategies and promising practices for addressing the critical problem of tobacco in the AA and NHPI communities.